2011
DOI: 10.1111/j.1462-2920.2011.02605.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic metabolism of a broad range of C1 compounds in the marine methylotrophic bacterium HTCC2181

Abstract: The 1.3 Mbp genome of HTCC2181, a member of the abundant OM43 clade of coastal bacterioplankton, suggested it is an obligate methylotroph. Preliminary experiments demonstrated that methanol and formaldehyde, but not other common C1 compounds such as methylamine, could support growth. Methanol concentrations in seawater are reportedly < 100 nM, suggesting either that the flux of methanol through plankton pools is very rapid, or that methanol may not be the primary growth substrate for HTCC2181. Therefore, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 61 publications
7
90
0
Order By: Relevance
“…PQQ MDH also occurs in many other Gram-negative methylotrophs (Nunn et al, 1989;Schmidt et al, 2010;Chistoserdova, 2011). Utilization of micro molar concentrations is known from M. extorquens AM1, and the marine methylotrophic strain HTCC2181 (Betaproteobacteria) (Giovannoni et al, 2008;Halsey et al, 2012). Strain HTCC2118 assimilates 10 mmol l À 1 methanol, which is substantially above observed minimal concentrations (0.002 mmol g soilDW À 1…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…PQQ MDH also occurs in many other Gram-negative methylotrophs (Nunn et al, 1989;Schmidt et al, 2010;Chistoserdova, 2011). Utilization of micro molar concentrations is known from M. extorquens AM1, and the marine methylotrophic strain HTCC2181 (Betaproteobacteria) (Giovannoni et al, 2008;Halsey et al, 2012). Strain HTCC2118 assimilates 10 mmol l À 1 methanol, which is substantially above observed minimal concentrations (0.002 mmol g soilDW À 1…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, it has been demonstrated that methylotrophs that are restricted to methanol as carbon source exhibit increased methanol assimilation rates when they codissimilate alternative monocarbon compounds (Halsey et al, 2012). Thus, it is likely that methanol utilizers in aerated soils are not restricted to ambient methanol utilization and occupy different ecological niches in regard to the alternative substrates they can metabolize (Kolb, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypes of the xoxF mutants strongly suggest their involvement in methanol metabolism, identifying them as likely methanol dehydrogenases, with redundant functions. Such a role has been previously proposed for XoxF proteins (22,23), and weak methanol dehydrogenase activity has been measured for a purified XoxF protein from Methylobacterium extorquens AM1 (24). It is assumed that, like the MxaFI methanol dehydrogenase, the immediate electron acceptor is a cytochrome c (12).…”
Section: Discussionmentioning
confidence: 99%
“…OM43 is a coastal species that is found associated with phytoplankton (Morris et al, 2006). Recent reports of high turnover rates for methanol in the ocean surface (Dixon et al, 2011), a report describing many alternative OM43 substrates (trimethylamine, trimethylamine oxide, dimethylamine and methyl chloride; Halsey et al, 2012), and a report that OM43 xoxF was 2.3% of the identified spectra in a productive coastal ocean metaproteome (Sowell et al, 2011), all suggest future studies will aim to understand this unusual organism.…”
Section: Living Streamlinedmentioning
confidence: 99%